The ten commandments [videorecording (DVD)] - Bernstein, Elmer (Paramount Pictures, 2017)
The story of the life of Moses from the Pharaoh's household through his life of leading his people to freedom. The Ten Commandments has stood the test of time as a cinematic masterpiece and one of the all-time great sweeping epic films.